2020
DOI: 10.1126/sciadv.aax9455
|View full text |Cite
|
Sign up to set email alerts
|

STING couples with PI3K to regulate actin reorganization during BCR activation

Abstract: The adaptor protein, STING (stimulator of interferon genes), has been rarely studied in adaptive immunity. We used Sting KO mice and a patient’s mutated STING cells to study the effect of STING deficiency on B cell development, differentiation, and BCR signaling. We found that STING deficiency promotes the differentiation of marginal zone B cells. STING is involved in BCR activation and negatively regulates the activation of CD19 and Btk but positively regulates the activation of SHIP. The activation of WASP a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Hence, fine-tuned control of STING retention/exit in and from the ER is key to regulate signaling. Intriguingly, it was recently reported that STING controls the accumulation of F-actin via WASP and PI3K in B cells, impacting BCR signaling ( 71 ). There is a strong rationale to predict more connections between actin and STING trafficking.…”
Section: Cgas-sting Trafficking and The Connection With The Cytoskeletonmentioning
confidence: 99%
“…Hence, fine-tuned control of STING retention/exit in and from the ER is key to regulate signaling. Intriguingly, it was recently reported that STING controls the accumulation of F-actin via WASP and PI3K in B cells, impacting BCR signaling ( 71 ). There is a strong rationale to predict more connections between actin and STING trafficking.…”
Section: Cgas-sting Trafficking and The Connection With The Cytoskeletonmentioning
confidence: 99%
“…Given the pro-apoptotic impact of high-doses of STING agonists on VEC (i.e. vasoablative) and immune cell populations ( 67 , 73 76 , 120 , 121 ), but the ability of low-dose regimens to promote VN and enhanced pro-inflammatory immune function in pre-clinical models, it might be anticipated that low-dose protocols will provide optimal immunotherapeutic benefits in these trials. While it is not clear that the formation of TLS represents an exploratory endpoint in these ongoing trial designs, one might expect that low-dose regimens of these next-generation STING agonists will prove effective in inducing de novo development of TLS or expansion of existing TLS within the tumor of treated patients.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…While the exact mechanism underlying this deficiency in CXCL13 production remains unclear, it could relate to the known regulatory action of STING signaling in B cells. For instance, the activation of STING in B cells via genetic engineering to express a constitutively activated form of STING or by treatment of B cells with STING agonists results in endoplasmic reticulum (ER)-associated degradation of membrane-bound immunoglobulin, muted BCR signaling via enhanced SHP1 phosphatase activity and increased rates of B cell apoptosis ( 74 76 ).…”
Section: Combination Sting Agonist Therapies May Be Required To Promote the Neogenesis Of Classical Mature Tls In The Tmementioning
confidence: 99%
“…The cGAS serves as a potent PRR for the recognition of cytosolic dsDNA in both plasmacytoid DCs (pDCs) and conventional DCs (cDCs), indicating their role in the generation of the potent T-cell-mediated immune response and the B cell-mediated Ab generation ( 20 ). In addition to this, STING also directly impacts adaptive immunity as its deficiency promotes the marginal zone B cell development and differentiation via activating B cell receptor (BCR) signaling ( 98 ). STING positively regulates SHIP-1 (SH2-containing inositol 5′polyphosphatase-1, that is required for B cell tolerance to self-antigens and dampens naïve and low-dose antigen-primed B cells) activation, but negatively regulates CD19 (a 95 kDa type 1 transmembrane protein of immunoglobulin superfamily that establishes a threshold for intrinsic B cell signaling via modulating BCR-dependent and independent signaling) and Bruton’s tyrosine kinase (Btk, essential for B cell development and function of mature B cells downstream to the BCR signaling) ( 98 101 ).…”
Section: Cgas-sting-based Host Cell Dna Recognitionmentioning
confidence: 99%
“…In addition to this, STING also directly impacts adaptive immunity as its deficiency promotes the marginal zone B cell development and differentiation via activating B cell receptor (BCR) signaling ( 98 ). STING positively regulates SHIP-1 (SH2-containing inositol 5′polyphosphatase-1, that is required for B cell tolerance to self-antigens and dampens naïve and low-dose antigen-primed B cells) activation, but negatively regulates CD19 (a 95 kDa type 1 transmembrane protein of immunoglobulin superfamily that establishes a threshold for intrinsic B cell signaling via modulating BCR-dependent and independent signaling) and Bruton’s tyrosine kinase (Btk, essential for B cell development and function of mature B cells downstream to the BCR signaling) ( 98 101 ). The BCR activation in the STING -/- B cells increases Wiskott-Aldrich syndrome protein (WASP, which activates downstream to the BCR signaling, links receptor signaling to the actin dynamic through actin-related proteins-2/3 (Arp2/3) complex, and also controls BCR mobility during activation) activation and F-actin accumulation via PI3K used by CD19-Btk axis as a central hub ( 98 , 102 ).…”
Section: Cgas-sting-based Host Cell Dna Recognitionmentioning
confidence: 99%